Research application of endoscopic ultrasound - fine needle aspiration in diagnosis pancreas tumors - Vinh, Khanh; Tran, Van Huy (Tạp chí Y Dược Huế, 2022)
Background: Pancreatic diseases is very multiform and complex, in which pancreatic tumors have often poor prognosis, especially pancreatic cancer. Early detection and diagnosis of pancreatic tumors have great significance in improving the quality of treatment and prognosis for patients. Endoscopic ultrasound has the advantage of high-frequency ultrasound, an optimal approach to provide a possibility of EUS-FNA. This is important evidence to confirm the diagnosis, guide to treatment and prognosis. This study was aimed at: (1) To describe the characteristics of the pancreatic tumor by endoscopic ultrasound; (2) To evaluate the efficacy and safety of endoscopic ultrasound fine needle aspiration in the diagnosis of pancreatic tumors. Subject and methods: Cross-sectional study concludes 41 pancreatic tumor patients, which indicated endoscopic ultrasound fine needle aspiration in Gastroenterology - Endoscopy Center, Hue University of Medicine and Pharmacy Hospital from 2/2010 to 10/2022. Results: The size of the tumor was more than 2cm, tumors in the pancreatic head accounted for 80.5% and solid tumors accounted for 80.5%. Besides, the main pancreatic duct dilatation accounts for 39.0%, the biliary tract dilatation accounts for 46.3%, pancreatic tumor invades adjacent organs accounts for 29.3%, vascular invasion accounts for 24.4%, with lymph nodes accounting for 51.2%. Endoscopic ultrasound-guide fine needle aspiration pancreatic tumor was performed in 37/41 cases (90.3%). Pathological of pancreatic tumor: pancreatic cancer is highest about 59.5%, benign pancreatic tumors accounted for 10.8%, mucinous cysts accounted for 5.4% and pancreatic tuberculosis accounted for 2.7%. The complication rate of the procedure was 5.4%. Conclusion: Endoscopic ultrasound fine needle aspiration pancreatic tumors showed relative safety and efficacy, the technical failure rate is very low.